2006
DOI: 10.1111/j.1440-1711.2006.01464.x
|View full text |Cite
|
Sign up to set email alerts
|

Fcγ receptor‐ligating complexes improve the course of experimental autoimmune encephalomyelitis by enhancing basal Th2 responses

Abstract: Summary IL-12p40 and macrophages are essential for the induction of disease in the mouse model of multiple sclerosis, experimental autoimmune encephalomyelitis. In this paper, we show that treatment of mice with opsonized erythrocytes, which have been shown to ligate Fcg receptors on macrophages and alter their cytokine profile, significantly delayed the onset of experimental autoimmune encephalomyelitis. This protection correlated to the induction of Th2 responses by autoreactive T cells, enhanced basal syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 28 publications
5
37
0
Order By: Relevance
“…Cells were cultured (10 6 cells/ml) in complete medium containing Dulbecco’s minimal essential medium, 10% FCS, 100 U/ml penicillin plus 100 µg/ml streptomycin, 10 mM Hepes, 2 mM L-glutamine, and 50 µM 2-mercaptoethanol (all from Invitrogen, Carlsbad, CA) and stimulated with MOG peptide (27 µg/ml) or MIS416 (20 µg/ml) for 72 or 48 hours, respectively. These doses were based upon previously published dose-response curves for MOG [14], [15] and MIS416 [12].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured (10 6 cells/ml) in complete medium containing Dulbecco’s minimal essential medium, 10% FCS, 100 U/ml penicillin plus 100 µg/ml streptomycin, 10 mM Hepes, 2 mM L-glutamine, and 50 µM 2-mercaptoethanol (all from Invitrogen, Carlsbad, CA) and stimulated with MOG peptide (27 µg/ml) or MIS416 (20 µg/ml) for 72 or 48 hours, respectively. These doses were based upon previously published dose-response curves for MOG [14], [15] and MIS416 [12].…”
Section: Methodsmentioning
confidence: 99%
“…This activation state can impair anti-microbial effector functions but has been shown to protect against pathology in pro-inflammatory disease models such as EAE and septic shock. Our previous work has shown that this activation state is protective during EAE, and this protection is dependent upon IL-4 [8]. However, it is unknown how the Th2 environment, promoted by type II-activated macrophages, is induced nor how this environment, once induced, affects the macrophage’s effector functions.…”
Section: Introductionmentioning
confidence: 99%
“…These macrophages produce less IL-12 and significantly more IL-10 than classical macrophages while producing similar levels of TNF-α and NO [6]. Although the expression of CD40 and PD-L1 are significantly reduced, type II-activated macrophages are effective antigen-presenting cells and promote the development of Th2 cells both in vitro and in vivo [3], [7], [8]. This activation state can impair anti-microbial effector functions but has been shown to protect against pathology in pro-inflammatory disease models such as EAE and septic shock.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the presence of type II‐activated macrophages promotes the differentiation of Th2 cells and subsequent IL‐4 production 5 . Earlier work in our laboratory has shown that in vivo administration of FcγR‐ligating immune complexes alone enhanced Th2 responses and protected mice from developing experimental autoimmune encephalomyelitis (EAE), an animal model for multiple sclerosis (MS) 6 …”
mentioning
confidence: 99%